In Vacuo Synthesis of Xanthan-gum-based Hydrogels with Different Vinyl Monomer Mixtures and their Swelling Behaviour in Response to External Environmental Conditions. Issue 1 (February 2013) - Mittal, Hemant; Jindal, Rajeev; Kaith, Balbir Singh; Berry, Shivani
This research paper deals with the in vacuo synthesis of pH- and temperature-sensitive hydrogels of xanthan gum with different vinyl monomer mixtures such as acrylamide-co-acrylic acid (AAm-co-AA), acrylamide-co-acrylonitrile (AAm-co-AN), and acrylamide-co-methacrylic acid (AAm-co-MAA), keeping acrylamide as the principal monomer. Different optimised reaction parameters for the graft copolymerisation of xanthan gum (Gx) with AAm were as follows: reaction time = 240 min; temperature = 60°C; amount of water = 25 mL; vacuum = 450 mmHg; pH = 7.0; [KPS] = 0.0068 mol L -1 ; [AAm] = 0.071 mol L -1 ; [MBA] = 0.138 mol L -1 . Thereafter, the optimised molar ratio of AAm AA, AAm AN, and AAm MAA, keeping AAm as the principal monomer, were (0.071+0.037) mol L -1, (0.071+ 0.040) mol L -1, and (0.071+0.051) mol L -1 respectively. Synthesised hydrogels were characterised by FT-IR, SEM, XRD, and TGA/DTA/DTG. The swelling capacity of hydrogels was investigated in deionised water. Moreover, the effect of the ionic strength of various cations (Na +, Ba +2, Fe +3, and Sn +4 ) and cationic charge on the swelling capacity of the hydrogels in different salt solutions was also studied, and the percentage swelling was found to decrease with increased ionic strength and cationic charge.